IMPLEMENTATION OF COUNTER-RADICALISATION IN PESANTREN SALAFIYAH SYAFI'IYAH OF BANUROJA GORONTALO - Ahmad Faisal; mukrimin mukrimin; Fikri H. Asnawi Fikri H. Asnawi (Al-Qalam, 2023)
This study describes and evaluates how the Pesantren (the Islamic Boarding School) Salafiyah Syafi'iyah of Gorontalo has fostered a movement away from radicalism among its students. The state promotion and action of structural counter-radicalism have reached only a few urban Indonesians. The majority, however, live in rural areas. This research used observation, interviews, and records. The data was then subjected to descriptive and critical analysis. This study showed that Pesantren have a significant role in preventing radicalisation in their local communities. This campaign has been ongoing for some time and is still strong due to efforts to strengthen academic, religious, and social cultures. Thus, it is necessary to combine the counter-radicalisation efforts of the state, which have focused on structural measures, with the cultural approach exemplified by the Pesantren communities. Maintaining and promoting the integration of all children in the country is important, as terrorism and other forms of radical thought and movement harm religion and the nation.